Implementasi Logika Fuzzy Untuk Pemeriksaan Gizi Berdasarkan IMT Pada Aplikasi Fitpriority - Mardhavi, Arif; Sihananto, Andreas Nugroho; Nurlaili, Afina Lina (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2025)
Public awareness of the importance of leading a healthy lifestyle and exercising hassignificantly increased in recent years. However, various issues such as a lack of understandingof proper exercise techniques and nutrition that do not align with fitness goals remain prevalent.To address these challenges, this study designs a web-based application called Fitpriority toconnect users with professional trainers. One of the main features of this application is anutritional status check based on Body Mass Index (BMI). This algorithm was chosen for itsability to tolerate small changes in nutritional values, unlike the rigid traditional logic methods.The study employs the Mamdani method to determine nutritional status through the processes offuzzification, implication function application, rule aggregation, and defuzzification using thecentroid method. Additionally, the System Usability Scale (SUS) method is used to assess theusability and user experience of the developed application. The results of this study are expectedto provide an effective solution for individuals aiming to achieve their fitness goals moreefficiently and comfortably, and to serve as a valuable tool for a wide range of users inmaintaining optimal physical health and fitness.